2013
DOI: 10.4236/am.2013.49169
|View full text |Cite
|
Sign up to set email alerts
|

Technical Components of Total Factor Productivity Growth in Malaysian Manufacturing Industry

Abstract: This article attempts to disaggregate and explore the components of TFP growth that contribute to changes in output, scale of production, and allocative efficiency and technical efficiency of the Malaysian manufacturing sector. The total factor productivity (TFP) concept defined as total output per unit of all inputs used in the production of an industry has gained a prominent place in academia. The investigation on TFP growth is obviously useful for identifying sources of output growth in the development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…A study on the TE of the food manufacturing industry in Malaysia by Nik Hashim and Basri (2004) found that the level of TE of the food manufacturing industry in the country is low, a similar finding to that of Ismail (2009). Therefore, the latest research on the level of TE and the determinants of technical inefficiency of electrical and electronic manufacturing firms using corporate-level data should be undertaken to increase the productivity of the industry in the future.…”
Section: Literature Reviewsupporting
confidence: 52%
“…A study on the TE of the food manufacturing industry in Malaysia by Nik Hashim and Basri (2004) found that the level of TE of the food manufacturing industry in the country is low, a similar finding to that of Ismail (2009). Therefore, the latest research on the level of TE and the determinants of technical inefficiency of electrical and electronic manufacturing firms using corporate-level data should be undertaken to increase the productivity of the industry in the future.…”
Section: Literature Reviewsupporting
confidence: 52%
“…However, studies, such as Sulaiman (2012), Mustapha et al (2013) and Ismail and Abidin (2017), have used data at the industry level. In addition, research on the determinants of technical inefficiencies has also been overlooked to measure efficiency as stated by Mahadevan (2002a), Mahadevan (2002b), Mahadevan (2002c) and Said et al (2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study mainly focusing on the concept of TFP, which is a measurement based on the economic theory of production. The theory of TFP widens the concept of single factor productivity, which is output per unit input (labor and capital), to more than one factor (Mustapa et al, 2013). The TFP change identifies shifts in the production function caused by underlying economic decisions and activities.…”
Section: Introductionmentioning
confidence: 99%